2022
DOI: 10.3390/cancers14184350
|View full text |Cite
|
Sign up to set email alerts
|

A Matched-Pair Analysis after Robotic and Retropubic Radical Prostatectomy: A New Definition of Continence and the Impact of Different Surgical Techniques

Abstract: Background: Radical prostatectomy is considered the gold-standard treatment for patients with localized prostate cancer. The literature suggests there is no difference in oncological and functional outcomes between robotic-assisted radical prostatectomy (RARP) and open (RRP). (2) Methods: The aim of this study was to compare continence recovery rates after RARP and RRP measured with 24 h pad weights and the International Consultation on Incontinence Questionnaire—Short Form (ICIQ-SF). After matching the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Notable urinary stress incontinence (>1 safety pad per day) was shown to be reported significantly less frequently in the RARP compared to the ORP group based on univariate analysis (14.6% vs. 24.9%; p = 0.001), which supports the results of d’Altilia et al [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Notable urinary stress incontinence (>1 safety pad per day) was shown to be reported significantly less frequently in the RARP compared to the ORP group based on univariate analysis (14.6% vs. 24.9%; p = 0.001), which supports the results of d’Altilia et al [ 15 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, some studies found some advantages associated with RARP, especially in terms of erectile function [ 9 , 10 , 11 , 14 ]. Based on a matched-pair analysis, d’Altilia et al demonstrated a higher proportion of patients with urinary incontinence following ORP compared to RARP [ 15 ]. In addition, soft criteria such as length of hospital stay and intraoperative blood loss have been shown to significantly improve with RARP as opposed to ORP [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rates have improved for RARP, reporting UC between 30 and 46.8% [ 7 , 9 ]. According to the ICIQ-SF score, the severity of incontinence in these studies ranged from slight to moderate [ 11 ]. Accruing and centralizing surgical experience have been promoted as a mean to improve patient outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) [ 8 ] has been consistently used for post-prostatectomy UC recovery evaluation [ 9 ]. Henceforth, employing both the ICIQ-SF and pad use has been shown to yield a better insight of postoperative UC and a more accurate demonstration of the differences between surgical techniques [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%